Study of Serum Electrolytes and Total Calcium Status in Patients with Acute Myocardial Infarction - Nirdhan Yadav; Surendra Marasini; Suprita Gupta; Satyam Prakash; Sanjay Kumar Sah; Amit Chandra Jha; Rohit Sah (Janaki Medical College Journal of Medical Science, 2025)
Background and objectives: Electrolyte imbalances are often seen following acute myocardial infarction (AMI). Since these electrolyte levels can be altered, they have significant effect on the prognosis of people with AMI. Among these, some studies have discovered a serum sodium imbalance in the initial phases of AMI. Thus, the aim of this study was to correlate the electrolytes level with cardiac parameters in Myocardial Infarction. Materials and Methods: The present study was an analytical cross-sectional study conducted on patients with AMI who visited the inpatient (Emergency and medicine) Department at NMCTH, Birgunj and Parsa, Nepal. A total of 100 patients with AMI were enrolled during the four-month study period from March 2025 to June 2025. The cardiac profile and serum electrolytes of the patients were measured using a Beckman Coulter AU 480, SENSA CORE ST 200 PRO and Getein 1100 immunofluorescence quantitative analyzer. Results: The non-parametric correlation analysis revealed that CK-MB and Troponin I had a strong negative correlation with sodium, potassium, calcium and age but CK-MB has strong positive correlation with Troponin-I and vice versa. Additionally, CK-MB was significantly correlated with sodium, calcium and Troponin-I but was not significantly correlated with potassium and age. Troponin-I was significantly correlated with potassium, Calcium and CK-MB but Troponin-I was not significantly correlated with sodium and age. Conclusions: This study revealed that electrolyte concentrations varied among patients with acute myocardial infarction (AMI). Serum level of sodium and potassium are correlated with cardiac biomarkers CKMB & troponin-I. Moreover, monitoring the serum sodium & potassium levels are can be helpful clinically for the treatment of AMI. Furthermore, serum calcium is also associated with CKMB & troponin I in AMI patients.